Acute effects of first generation calcium antagonists on left ventricular diastolic functions in healthy individuals and in essential hypertension patients - Isik, A.; Luleci, C.; Celiker, H.; Arslan, N.; Donder, E.; Alasehirli, E. (My University, 1992)
[Abstract Not Available]
Keywords: calcium antagonist; diltiazem; nifedipine; verapamil; adult; article; blood pressure; clinical article; controlled study; echocardiography; essential hypertension; female; heart left ventricle function; hemodynamics; human; intravenous drug administration; male; oral drug administration